Corporate Tax Avoidance in Indonesia: Ownership Structure and Executive Incentives - Sudarmanto, Didik; Kartika Sari, Putri Malynda; Aipah, Aipah; Lestari, Heny Setyo; Margaretha, Farah (Moneter: Jurnal Keuangan dan Perbankan, 2024)
The purpose of this study is to close the gap in the literature by examining the connection between tax evasion in Indonesia, executive incentives, company governance quality, and family ownership. It is anticipated that the study's findings would help company executives and policymakers better understand corporate governance and curtail tax evasion. The results of this study can help policymakers and regulators in Indonesia create more effective regulations to boost corporate governance and increase tax compliance. Quantitative approaches are the research approach that is being applied. The independent variables of family ownership, corporate governance, and executive incentives have little impact on tax avoidance, according to the findings of statistical tests using panel data model estimate in partial T test testing. The movement or change in the independent variables in this study is unrelated to the tax avoidance ratio.